Effect of Work Culture and Work Motivation On Employee Performance Through Job Satisfaction at OJK Malang - SAPUTRA, Asep Dana; SUHARSONO, Riyanto Setiawan (PT Keberlanjutan Strategis Indonesia, 2021)
The purpose of this study was to determine the effect of work culture and work motivation on employee performance through job satisfaction at OJK Malang. The population in this study were all employees at OJK Malang as many as 55 respondents using the census method. The data analysis technique used is descriptive analysis technique using path analysis equation model. The results of this study Work Culture and Work Motivation have a significant effect on Job Satisfaction at the Malang OJK Office, this means that the higher the Work Culture and Work Motivation, the Job Satisfaction will increase. Job Satisfaction has a significant effect on Employee Performance at the Malang OJK Office. Work Culture and Work Motivation have a significant effect on Employee Performance through Job Satisfaction at the Malang OJK Office, this means that the higher Job Satisfaction caused by high Work Culture and Work Motivation, it can improve Employee Performance